Taxpayer conplience : e-filling system and taxpayer characteristics trait contribution at Sub Distric Parongpong - Nelly Grasella Simanjuntak; Rolyana Ferinia (Jurnal Mantik, 2023)
The objective of this study is to evaluate the influence of e-filing technology and taxpayer attributes on taxpayer compliance. The selected research methodology for this study is quantitative, employing a correlational design. The data collection process employed non-probability sampling techniques. The research instrument employed in this study was a questionnaire that was administered only to a sample of 100 taxpayers residing in Parongpong District. The research employed the data analysis technique of Structural Equation Modeling (SEM) utilizing the smartPLS software. The empirical evidence suggests that the introduction and utilization of the e-filing system does not yield a substantial impact on taxpayer compliance. Nevertheless, it can be observed that the implementation of the e-filing system has yielded favorable outcomes in terms of taxpayer attributes. In addition to this, it was observed that the characteristics of taxpayers exert a significant impact on tax compliance. Moreover, it is evident that the electronic filing system, by influencing the attributes of taxpayers, plays a role in augmenting tax compliance. The research presented in this study highlights the originality of utilizing tax e-filing as a means to enhance the attributes of taxpayers, including their traits, obedience, and discipline.